The envelope method and substrate wetting in the germination test of onion seeds - Jeromini, Tatiane; Muniz, Roberta; Silva, Givanildo; Martins, Cibele (Revista Ciência Agronômica, 2018)
The Rules for Seed Analysis reports the use of a paper envelope in germination tests, but without any description of the exact method. The objective of this study was to evaluate the viability of the envelope method and the optimal level of substrate wetting when performing germination tests of onion seeds. The study was performed in two stages. In the first stage, a batch of seeds was evaluated using two seeding methods (on paper and in a paper envelope) and five levels of substrate wetting with differing amounts of water: 1.5, 2.0, 2.5, 3.0, and 3.5 times the dry mass of the paper. A completely randomized design was used in a 2×5 factorial scheme. In the second stage of the study, the two seeding methods mentioned in the prior were tested in eight seed batches using a completely randomized design and a 2×8 factorial scheme. The degree of moisture, germination, and the first count of germination were evaluated. The time spent for the installation, seeding, counting, and disassembling of the germination test were determined. It was concluded that the envelope method is fit for use in onion seed germination tests. The optimal amount of water to add to the substrate is 2.5 times the dry mass of the paper substrate. The envelope method is fast, practical, and more efficiently uses space within germinator chambers, making it easily incorporable into routine tests within seed analysis laboratories.